Insight gained from responses to surveys on reference dosimetry practices. (11th April 2017) - Muir, Bryan; Culberson, Wesley; Davis, Stephen; Kim, Gwe‐Ya; Huang, Yimei; Lee, Sung‐Woo; Lowenstein, Jessica; Sarfehnia, Arman; Siebers, Jeffrey; Tolani, Naresh
Abstract: Purpose: To present the results and discuss potential insights gained through surveys on reference dosimetry practices. Methods: Two surveys were sent to medical physicists to learn about the current state of reference dosimetry practices at radiation oncology clinics worldwide. A short survey designed to maximize response rate was made publicly available and distributed via the AAPM website and a medical physics list server. Another, much more involved survey, was sent to a smaller group of physicists to gain insight on detailed dosimetry practices. The questions were diverse, covering reference dosimetry practices on topics like measurements required for beam quality specification, the actual measurement of absorbed dose and ancillary equipment required like electrometers and environment monitoring measurements. Results: There were 190 respondents to the short survey and seven respondents to the detailed survey. The diversity of responses indicates nonuniformity in reference dosimetry practices and differences in interpretation of reference dosimetry protocols. Conclusions: The results of these surveys offer insight on clinical reference dosimetry practices and will be useful in identifying current and future needs for reference dosimetry.